Dickens - Barber, Nicola (Tunbridge Wells Ticktock, 2001)
The life and times of this great novelist and his masterpieces. This series provides a fascinating introduction to the lives and works of major writers and the historical cultural and literary contexts in which they wrote.
Include Illustrations and Index.
Keywords: Novelists, English -- Dickens, Charles, 1812-1870